Nuevos estudios sencillos: for guitar - Brouwer, Leo 1939- (Chester music, 2002)
Leo Brouwer's Nuevos Estudios Sencillos is a collection of short Guitar pieces in the style of composers such as Debussy, Prokofiev, Piazzolla, and more.